COMMUNICATIVE QUALITIES OF SPEECH (Scientific journal of the Fergana State University, 2025)
The communicative qualities of speech are key characteristics that ensure successful interaction between individuals. This paper examines the main qualities, such as clarity, accuracy, logicality, consistency, expressiveness, and appropriateness, and their role in various communicative situations. Special attention is given to how these qualities influence the effectiveness of communication and reduce the risk of misunderstanding. These characteristics are important in both everyday conversations and professional or academic contexts.